Understanding the Anion‐Templated, OSDA‐Free, Interzeolite Conversion Synthesis of High Silica Zeolite ZK‐5. Issue 56 (8th August 2022) - Lozinska, Magdalena M.; Bruce, Elliott L.; Mattock, James; Chitac, Ruxandra G.; Cox, Paul A.; Turrina, Alessandro; Wright, Paul A.
Abstract: High silica zeolite ZK‐5 (framework Si/Al=4.8) has been prepared by interzeolite conversion from ultrastable zeolite Y via a co‐templating route using alkali metal cations and nitrate anions but without organic structure directing agents. The mechanism, which involves zeolite framework – alkali metal cation – nitrate anion ordering, has been established by a combination of chemical and thermal analyses, Raman spectroscopy, computational modelling, and X‐ray powder diffraction. Ammonium exchange gives ZK‐5 with occluded ammonium nitrate and subsequent heating gives microporous zeolite ZK‐5. Abstract : High silica forms of the zeolite ZK‐5 are prepared by an interzeolite conversion using inorganic cations and anions as templates. K + and Cs + cations and NO3 − anions self‐assemble within its lta and pau cages with a high degree of space filling and exchange with NH4 + followed by heating gives a microporous solid. This approach offers an alternative and organic structure directing agent‐free route to directing zeolite synthesis.